Living Value Pada Penderita Kusta (Intuisi : Jurnal Psikologi Ilmiah, 2012)
Abstrak. Penelitian ini bertujuan untuk mengetahui bagaimana living value pada penderita kusta. Penelitian menggunakan metode kualitatif fenomenologis dan living value pada penderita kusta sebagai unit analisis. Responden berjumlah tiga orang dan empat informan penunjang. Teknik pengumpulan data menggunakan teknik wawancara dan observasi. Teknik keabsahan data dengan ketekunan pengamatan di lapangan dan teknik triangulasi.Hasil dari penelitian ini menunjukkan bahwa penyakit kusta memberikan perubahan signifikan tidak hanya secara fisik tetapi juga keterpurukan secara psikis dalam diri individu. Penderita kusta mengalami perubahan-perubahan pada nilai-nilai hidupnya dikarenakan penderitaan yang mereka alami. Sikap yang ditunjukkan karena penderitaan tersebut ternyata sangat dipengaruhi oleh motivasi dalam dirinya sendiri yang ditunjukkan dengan adanya visi hidup yang kuat dalam diri penderita, serta adanya pemaknaan yang baik terhadap penderitaan yang dialami. Kedewasaan individu dalam memaknai hidup ini tidak dipengaruhi oleh usianya. Pemaknaan dalam diri individu memberi pengaruh dalam bersikap. Dukungan dari orang-orang terdekat juga merupakan salah satu faktor vang mempengaruhi. Rasa dicintai dan mencintai yang besar akan membuat individu semakin kuat, dan akhirnya menunjukkan sikap-sikap yang positif dalam menghadapi setiap hal dalam hidupnya. Pemahaman yang positif akan nilai-nilai hidupnya menambah kesejahteraan dalam diri individu.Adapun saran yang disampaikan kepada pihak Rumah Sakit Khusus Kusta Kediri adalah untuk lebih memberikan perhatian khusus terhadap pemulihan psikis pasien. Telah diketahui bahwa pemahaman yang positif akan nilai-nilai hidup akan menmbah kesejahteraan dalam diri individu maka akan sangat baik bila diadakan pelatihan akan nilai-nilai hidup oleh peneliti selanjutnya. Bagi keluarga penderita kusta, agar tetap memberi dukungan penuh kepada penderita kusta dan menambah informasi dan pengetahuan tentang penyakit kusta sehingga dapat menjadi partner yang baik dalam bekerja sama dengan petugas kesehatan untuk kesembuhan dan pemulihan penderita baik secara fisik maupun secara psikis.Kata Kunci: living value Abstract. Changes in one's life situation will affect all aspects of his life. Often the attitude shown in the face of bad things are despair and loss of zest for life. These attitudes illustrate the value of individual lives within it. Living life value or value is a conception that implicitly or explicitly distinguish individuals or groups and has a specificity that may affect the selection of a way for individuals or groups in achieving its intended purpose, value itself can not be separated from human life, because values are formed and held after going through a long process, namely as a result of individual interaction with the circumstances and environment. For leprosy patients, suffering not only caused by the illness in her body but also the stigma in society about leprosy that causes the emergence of attitudes of society towards discriminative lepers. This study aims to determine how to value living in leprosy patients. Research using qualitative methods of phenomenology and living value in leprosy patients as the unit of analysis. Respondents numbered three and four informants supporter. Data collection techniques using interview and observation techniques. Technical data validity by persistent observation in the field and triangulation techniques.The results of this study indicate that leprosy provide a significant change not only physically but also psychologically slump within the individual. Leprosy patients experienced changes in the values of life due to their sufferings. The attitude shown by the suffering that was heavily influenced by a motivation in itself that indicated the presence of a strong vision of life in patients, as well as a good meaning to the suffering endured. Individual maturity of life is not affected by age. Meaning within the individual to give effect in attitude. Support from the closest people too is one of the factors that influence. A sense of being loved and loving that big will make the individual stronger, and finally showed positive attitudes in facing every thing in his life. Understanding the positive values of life will add to the welfare of the individual self.The advice submitted to the Special Hospital Leprosy Kediri is to give more attention to the psychological recovery of patients. It is known that a positive understanding of the values of life will add to the welfare of individuals within it will be very good if the training will be held values to live by subsequent researchers. For families of leprosy patients, in order to continue giving full support  to sufferers of leprosy and add information and knowledge about leprosy so that it can be a good partner in working with health officials to healing and recovery of the patient both physically and psychologically.